DECISION-MAKING TOOL FOR PROPER SLUDGE DEWATERING IN PALESTINE - Salahat, Anas (An-Najah National University, 2025)
In Palestine, managing municipal sewage sludge (MSS) is becoming one of the most significant environmental issues. Sludge generation has steadily increased as a result of population growth and the quick construction of wastewater treatment facilities. Sludge's final treatment and sustainable use, however, are still quite limited, and it is typically left unmanaged. This puts society, the environment, and public health at risk. Additionally, there is a glaring knowledge and decision-making gap because so few research studies have addressed this issue in Palestine. By creating a useful tool to select the best sludge dewatering method and offering suggestions for wastewater treatment facilities, this study aims to assist Palestinian decision-makers. To aid in long-term planning and management, it is also crucial to forecast future sludge volumes at the Nablus West Wastewater Treatment Plant. The study employed two primary methods. First, various dewatering techniques were compared using the Analytic Hierarchy Process (AHP) according to social, environmental, and economic factors. After gathering information from published research and reports, it was examined and modified in consultation with subject-matter specialists and engineers. Second, the study estimated sludge quantities for the upcoming decades by analyzing recorded operational data from Nablus West WWTP along with design parameters and population projections. To help choose the best sludge drying techniques, a Python-based decision support tool was created. The tool incorporates economic, environmental, and technical factors into an organized framework for making decisions based on multiple criteria. It makes it possible to compare different drying options objectively by using systematic weighting and scoring procedures. In sludge management planning, this method encourages more open, consistent, and data-driven decision-making. According to the AHP analysis's findings, sludge dewatering beds are the best choice for wastewater treatment facilities in Palestine. This approach struck the best possible balance between social acceptance, environmental safety, and cost. Furthermore, the forecasting analysis indicated that Nablus West WWTP's sludge production would rise sharply in the future. The study concludes that, given the present situation, Sludge dewatering beds continue to be the most environmentally friendly option for Palestinian conditions. The ongoing rise in sludge production, however, highlights the pressing need for improved resource allocation and planning. Engineers, officials, and legislators can use the developed decision-making tool to help them
أداة لصنع القرار بشأن تقنيات تجفيف الحمأة المناسبة لفلسطين